Rhizosphere Bacterial Community Response to Continuous Cropping of Tibetan Barley - Yao, Youhua; Yao, Xiaohua; An, Likun; Bai, Yixiong; Xie, Deqing; Wu, Kunlun (Frontiers in Microbiology, 2020)
Long-term continuous cropping influences the nutrient of soil and microbiome of the rhizosphere, resulting in the yield decrease of crops. Tibetan barley is a dominant cereal crop cultivated at high altitudes in Tibet. Its growth and yield are negatively affected by continuous cropping; however, the response of the rhizosphere microbial community to continuous cropping remains poorly understood. To address this question, we investigated the bacterial community structure and conducted predictive functional profiling on rhizosphere soil from Tibetan barley monocropped for 2–6 years. The results revealed that long-term continuous cropping markedly decreased total nitrogen and available nitrogen in rhizosphere soil. Illumina high-throughput sequencing of 16S rRNA genes indicated that the bacterial community was altered by continuous cropping; operational taxonomic units (OTUs), Shannon index, and Faith Phylogenetic Diversity decreased with increasing monocropping duration. Relative abundances of family Pseudomonadaceae, Cytophagaceae, and Nocardioidaceae were significantly increased, while those of Chitinophagaceae and Sphingomonadaceae were significantly decreased (all p < 0.05). Besides, continuous cropping significantly increased the abundance of bacteria associated with chemoheterotrophy, aromatic compound degradation, and nitrate reduction (p < 0.05). Generalized boosted regression model analysis indicated that total nitrogen was the most important contributor to the bacterial community diversity, indicating their roles in shaping the rhizosphere bacterial community during continuous cropping. Overall, continuous cropping had a significant impact on the structure of bacterial communities in rhizosphere soil of Tibetan barley, and these results will improve our understanding of soil bacterial community regulation and soil health maintenance in Tibetan barley farm systems.